Improving Social Studies Understanding Through Simple Experimental Media in Elementary Schools - Desty Anggreany; Ilyas Idris; Andi Nurhasanah (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2026)
Low student understanding in Science and Social Studies (IPAS) learning remains a common problem in elementary schools, especially in abstract materials such as the water cycle. Learning activities that are still dominated by lecture methods make students less active and less directly involved in the learning process. This study aimed to describe the implementation of simple experimental media and analyze the improvement of fifth-grade students’ understanding at SDN 182/VII Pasar Pelawan III in IPAS learning. This research used Classroom Action Research (CAR) based on the Kemmis and McTaggart model, conducted in two cycles consisting of planning, implementation, observation, and reflection stages. The research subjects were 19 fifth-grade students. Data were collected through observation, tests, interviews, and documentation. Data analysis used descriptive quantitative and qualitative techniques. The findings showed that the implementation of simple experimental media significantly improved students’ understanding. The average student score increased from 64.47 in the pre-cycle to 71.44 in cycle I and increased again to 81.57 in cycle II. Student learning completeness also improved from 32% to 64% and finally reached 90% in cycle II. In addition, teacher and student activities increased from 79.57% to 93.18%. These findings indicate that simple experimental media effectively create more active, meaningful, and contextual learning experiences.